MEMUTUS PIDANA MATI PADA KORUPTOR, ADIL ATAU TIDAK - Luvi Andiansyah; Nurul Fitria Hapsari Mamesah; Hudi Yusuf (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Talking about corruption, many people in the community are rife and annoyed by the existence of this corruption, various ways in which corruptors carry out corruption in this country to the point that people no longer trust law enforcers in this country. For various reasons, corruption cases escape legal prosecution. The impacts resulting from corruption are very dangerous, one of which is the decline in the national economy. Efforts to eradicate corruption are solely through prosecuting corruption, even though what is currently necessary is everyone's awareness of obeying corruption laws. There are quite a lot of regulations regarding corruption in Indonesia, but the results are still not satisfactory, especially the return of funds from the proceeds of corruption.